EDUKASI PENCEGAHAN PERNIKAHAN DINI MELALU PROGRAM LITERASI DI SMP 18 DESA NUMBING - Sari, Nila Permata; Abniarti, Nia; Nabila, Naiya; Alyamonica, Nicky; Putri, Nelfa Riana; Sapitri, Nor; Panjaitan, Octavia Veronica; Sipahutar, Lidya Febiola; Syakina, Nor; Irawan, Dody (Universitas Mataram, 2025)
Marriage is a bond intended to form a family. However, the phenomenon of early marriage still often occurs in society, which can have various negative impacts. Teenagers are the future leaders of the nation who must understand the impacts of early marriage so that they can focus more on their future rather than getting married at an immature age. Through community service activities, namely the early marriage prevention socialization program at SMP 18 Bintan, it is hoped that students will gain additional insight. The activity method used the Deming cycle model through four stages, namely planning, implementation, evaluation, and follow-up. The activity was carried out with an out-class approach in the form of socialization, interactive discussions, material delivery, as well as pre-tests and post-tests to measure student understanding. The results of the activity showed a significant increase in students' understanding of the material presented. This can be seen from the post-test results on statements regarding economic problems as one of the factors causing early marriage, where the majority of students (60%) answered “agree,” while the rest answered “strongly agree” (14%), ‘disagree’ (14%), and “strongly disagree” (12%). This data shows an improvement in understanding compared to the pre-test results. The results of the activity showed an increase in students' understanding of early marriage. Thus, this activity is expected to be one of the preventive measures to reduce the rate of early marriage in the future. Keywords: Prevention of early marriage, Factors, Impact